Elementos para una propuesta de política pública sobre el uso del tiempo como un factor protector de la salud mental en jóvenes del departamento de Nariño - Ojeda Rosero, Dayra Elizabeth; Sánchez Martínez, Nubia Rocio (Universidad y Salud, 2007)
A research about the community perception of time use was carried out. Four focal groups conformed by adolescents, young adults, older adults and community leaders, as well as individual interviews to people from different institutions, were carried out in three characteristic municipalities of Nariño Department, Colombia, Tumaco, La Unión and Pasto. Activities in every dimension of the Munné & Codina model (leisure, Psychobiological, sociocultural and socioeconomical) were identified, as well as issues related to the chronosystem of the Bronfrenbrenner bioecological model. There were proposed some usful subjects for public policy related to time use in the context of freedom respect and the social responsability for making up viable, sustainable and relevant alternatives with easy Access for population, integrating different social sectors and coherent with the cultural characteristics of the region.